Fiscal Decentralization and the Challenge of Hard Budget Constraints - Jonathan Rodden, Gunnar S. Eskeland, and Jennie Litvack (The MIT Press, 2003)
This book is the product of a multicountry research project at the World Bank aimed at understanding the institutional settings in which decentralization may lead to large fiscal deficits and macroeconomic instability. The project was undertaken by the Decentralization Thematic Group, which found a significant gap in knowledge regarding the macroeconomic risks associated with decentralization. Not until there is a better understanding of how and why decentralization poses risks to macroeconomic stability can governments begin to design policies and institutions to safeguard against those risks. The study develops an analytical framework for considering the issues related to soft budget constraints for state and local governments, including the institutions, history, and policies that drive expectations for bailouts among subnational governments. Four mechanisms for disciplining subnational governments—fiscal, financial, political, and land markets—are developed and applied to each of the eleven country case studies (Argentina, Brazil, Canada, China, Germany, Hungary, India, Norway, South Africa, Ukraine, and the United States). While recent econometric studies and scattered case studies allude to the complexity of hard budget constraints, this is the first in-depth look at a wide range of institutions that individually and collectively affect subnational discipline. Including developed and developing countries in the same study is important since the latter provide a historical perspective unavailable in many newly decentralizing developing countries. The policy implications of the study are very strong, playing directly into the long-standing debate (in which the World Bank, International Monetary Fund, and many academics have participated) between market and hierarchical mechanisms in the support of fiscal discipline under decentralization. The study concludes that this will often be a false dichotomy. In practice, most countries, and virtually all developing countries, will require both in order to maintain fiscal discipline and derive some efficiency gains. The cases provide ample examples of different combinations of mechanisms that have resulted in varying degrees of success. Expectations about extraordinary fiscal support from the central government are formed not only by whether there is a history of bailouts, but also by cues embedded in a variety of fiscal, political, and financial institutions. These institutions range from the basic architecture of government, like the separation of powers and the fiscal strength of the central government, to specific rules governing municipal bankruptcies and the distribution of intergovernmental transfers. Rather than portraying bailout episodes merely as regrettable failures, several of the cases suggest that if unavoidable bailouts are properly structured, they present opportunities to reform the underlying institutions that create bad incentives. The editors conclude that successful market discipline is not likely to appear instantly in newly decentralizing countries, but can emerge from a gradual evolutionary experience that starts with carefully crafted rules and oversight.